Warm Compress Reduced Pain Intensity of Arthritis Rheumatoid for Elderly People; Pre- and Post-test Design Study - ., Agussalim; Lorica, Josephine (KnE Life Sciences, 2019)
Arthritis Rheumatoid (AR) is an autoimmune disease showing erosive of symmetric joint. It sometimes refers to many systems disturbances inside our bodies. The progressivity of AR has chronic fluctuation in daily life. AR can increase mortality risk, especially for chronic disabilities. This study aims to understand the effect of warm compress on the pain intensity of AR cases for elderly people. The method used in this study was a quasi-experimental one. The sampling method used was a purposive technique. The total number of respondents was 10, with 5 as the interventional arm of the study and 5 as the control arm. This study was conducted between February and July 2014. A paired t-test was used to identify whether the sample means for those in the intervention arm was statistically different from the average of the sample means drawn from those drawn from the control group presumed to be from the general elderly population who do not benefit from the particular intervention of a warm compress. What the author wanted to conclude on was whether the two samples at hand actually differ significantly from each other. The intensity of pre- and post-intervention using parametric statistics following the application of warm compress was noted and used as a basis of comparison. The result of the statistics formula showed the effectiveness of warm compress in decreasing the AR pain, the t-test was 6.000 and the p-value was lower than 0.05. It can be summarized that warm compress can be used to decrease pain intensity for elderly people with AR. Discussion – the result of this study can be used as a reference to conduct care among elder people who are affected by AR. People living in the community area should help their family member with AR on first aid.